Anatomic Relationships of the Distal and Proximal Radioulnar Joints Articulating Surface Areas and of the Radius and Ulna Bone Volumes – Implications for Biomechanical Studies of the Distal and Proximal Radioulnar Joints and Forearm Bones - Malone, Paul S. C.; Shaw, Oliver G.; Lees, Vivien C. (Frontiers in Bioengineering and Biotechnology, 2016)
Background Previous work from this laboratory has evidenced the biomechanical role of forearm osseoligamentous structures in load transfer of applied forces. It has shown that transmitted forces across the distal radioulnar joint (DRUJ) and proximal radioulnar joint (PRUJ) are similar though not identical under axial loading conditions. The purpose of the study was to assess the articulating surface areas of the radioulnar joints and the volumes of the forearm bones addressing the hypothesis that there may be anatomic adaptations that reflect the biomechanical function of the integrated forearm unit. Methods The articulating surface areas of PRUJ and DRUJ were assessed using a laser scanner in 24 cadaver forearms. The articulating joint surfaces were additionally delineated from standardized photographs assessed by three observers. The surface areas of matched pairs of joints were compared on the null hypothesis that these were the same within a given forearm specimen. An additional 44 pairs of matched forearm bone volumes were measured using water displacement technique and again compared through statistical analysis (paired sample t-test, and Bland Altman analysis). Results The findings of this study are that the articulating surface areas of the DRUJ and PRUJ as well as the bone volumes are significantly different and yet strongly correlated. The paired sample t-test showed a significant difference between the surface areas of the DRUJ and PRUJ (p<0.05). The PRUJ articulating surface area was marginally larger than the DRUJ with a PRUJ : DRUJ ratio of 1.02. Paired sample t-test showed a significant difference between the two bone volumes (p<0.01) with a radius to ulna bone volume ratio of 0.81. When the olecranon was disregarded, radius volume was on average 4% greater than ulna volume. Conclusions This study demonstrated defines the anatomical relationships between the two forearm bones and their articulating joints when matched for specimen. The data obtained are consistent with the theory of integrated forearm function generated from published biomechanical studies.